Microbiome assembly and maintenance across the lifespan of bumble bee workers. Issue 3 (22nd November 2022) - Hammer, Tobin J.; Easton‐Calabria, August; Moran, Nancy A.
Abstract: How a host's microbiome changes over its lifespan can influence development and ageing. As these temporal patterns have only been described in detail for a handful of hosts, an important next step is to compare microbiome succession more broadly and investigate why it varies. Here we characterize the temporal dynamics and stability of the bumble bee worker gut microbiome. Bumble bees have simple and host‐specific gut microbiomes, and their microbial dynamics may influence health and pollination services. We used 16S rRNA gene sequencing, quantitative PCR and metagenomics to characterize gut microbiomes over the lifespan of Bombus impatiens workers. We also sequenced gut transcriptomes to examine host factors that may control the microbiome. At the community level, microbiome assembly is highly predictable and similar to patterns of primary succession observed in the human gut. However, at the strain level, partitioning of bacterial variants among colonies suggests stochastic colonization events similar to those observed in flies and nematodes. We also find strong differences in temporal dynamics among symbiont species, suggesting ecological differences among microbiome members in colonization and persistence. Finally, we show that both the gut microbiome and host transcriptome—including expression of key immunity genes—stabilize, as opposed to senesce, with age. We suggest that in highly social groups such as bumble bees, maintenance of both microbiomes and immunity contribute to inclusive fitness, and thus remain under selection even in old age. Our findings provide a foundation for exploring the mechanisms and functional outcomes of bee microbiome succession.